Rebels without a clue? Experimental evidence on partial cartels - Georg Clemens; Holger A. Rau (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper provides experimental evidence on the formation of partial cartels with endogenous coordination. Firms face a coordination challenge when a partial cartel is to be formed as every firm is better off if it is not inside the cartel but is a free-riding outsider. We introduce a three-stage mechanism with communication which facilitates the formation of a cartel and respectively allows the formation of a partial cartel. All-inclusive cartels are always formed. We find that partial cartels are frequently rejected out-of-equillibrium if moutside firms profit excessively from the formation of the cartel.
Keywords: C92; D02; L41; 330; Partial Cartels; Coordination; Communication; Experiment